Inequality in EU Crisis Countries: How Effective Were Automatic Stabilisers? - Tim Callan; Karina Doorley; Michael Savage (Institute of Labor Economics (IZA), 2018)
The Great Recession and the widespread adoption of fiscal austerity policies have heightened concern about inequality and how well tax-benefit systems redistribute. We examine how the distribution of income in the EU countries which were hardest hit during the recession evolved over this time. Using and extending a recently developed framework (Savage et al., 2017), the overall change in income inequality is decomposed into parts attributable to the change in market income inequality, changes in discretionary tax-benefit policy and automatic stabilisation effects. We implement this approach using the microsimulation software, EUROMOD, linked to EU-SILC survey data. Automatic stabilisation effects, particularly through benefits, are found to play an important role in reducing inequality in all the crisis countries. Their role is less important if we focus on the working age population only, due to the relative importance of old-age benefits in southern European welfare systems. Discretionary policy changes also contributed to reductions in inequality, but to a much lesser extent.
Keywords: H24; D31; D63; 330; inequality; decomposition; great recession; discretionary policy; automatic stabilisation